EMPLOYEE PERFORMANCE VIEWED FROM WORK DISCIPLINE, INFORMATION TECHNOLOGY, ORGANIZATIONAL CULTURE AND WORK ENVIRONMENT (STUDY ON DUKCAPIL SERVICE, KLATEN DISTRICT) - Rudy Widodo; Sudarwati Sudarwati; Istiatin Istiatin (Jurnal Ilmiah Global Education, 2023)
The objective of this study is to assess the impact of work discipline, information technology, organizational culture, and work environment on employee performance at the Dukcapil Office of Klaten Regency, both collectively and individually. The present study employs a quantitative research design. The study population consisted of 65 individuals who were operators employed at the Dukcapil Office of Klaten Regency. The provided sample is a subset that is indicative of the larger population under investigation (Arikunto, 2019: 109). The study utilized a census sampling technique to collect data from a total of 65 respondents. The process of gathering data through the utilization of a questionnaire. The data analysis technique employed in this study involved the application of statistical analysis methods, specifically the utilization of multiple linear regression test, F test, t test, and the coefficient of determination. The findings of the study indicate that work discipline, information technology, organizational culture, and work environment have a partial influence on the performance of employees at the Dukcapil Office of Klaten Regency. Based on the findings of this study, it is recommended that the Klaten Regency Dukcapil Office enhance work discipline, information technology, organizational culture, and the prevailing work environment. These improvements are expected to result in an increase in employee performance, surpassing previous levels.